2008
DOI: 10.1139/b08-066
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between reserve mobilization and regulation of nitrate uptake during regrowth of Lolium perenne L.: putative roles of amino acids and carbohydrates

Abstract: Louahlia, S., Laine, P., Macduff, J. H., Ourry, A., Humphreys, M. O., Boucaud, J. (2008). Interactions between reserve mobilization and regulation of nitrate uptake during regrowth of Lolium perenne L.: putative roles of amino acids and carbohydrates. ?Canadian Journal of Botany, 86, (10), 1101-1110. (now Botany) IMPF: 01.08 RONO: 1310 3001In most forage grass and legume species the recovery of leaf growth following severe defoliation depends on mobilization of carbon and nitrogen reserves from the remaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 48 publications
6
24
0
Order By: Relevance
“…We observed that AA content in young and old leaves and in roots decreased as a result of N deficiency (Fig. 2), which is consistent with a report that N deprivation decreased AA content in perennial ryegrass roots (Louahlia et al, 2008). Free AAs were the predominant storage compounds of reserve N for the regrowth of the bushgrass (Calamagrostis epigejos) after defoliation (Kavanová and Gloser, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that AA content in young and old leaves and in roots decreased as a result of N deficiency (Fig. 2), which is consistent with a report that N deprivation decreased AA content in perennial ryegrass roots (Louahlia et al, 2008). Free AAs were the predominant storage compounds of reserve N for the regrowth of the bushgrass (Calamagrostis epigejos) after defoliation (Kavanová and Gloser, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…In the roots, the NAD + -dependent GDH deamination activity decreased as a result of 28-d N deficiency in comparison with the +N treatment. Previous studies have shown that N deficiency stimulated export of assimilates to roots of darnel (Lolium temulentum) (Powell and Ryle, 1978) and increased root watersoluble carbohydrate of perennial ryegrass (Louahlia et al, 2008). The lower deamination activity observed in roots of N-deficient plants in the present study may suggest that a higher level of carbohydrate in the roots of -N plants may suppress the deamination activity, whereas a lower level of carbohydrate in the roots of +N plants may stimulate the deamination activity.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, N deficiency significantly decreased essential amino acids, including Lys, Phe, isoleucine (Ile), tryptophane (Trp), leucine (Leu), and valine (Val) content, and nonessential amino acids, consisting of glutamic acid (Glu), aspartic acid (Asp), Gly, argnine (Arg), and proline (Pro) content in both cultivars (Table 4). The general downregulation of amino acids in N-starved plants is expected and in agreement with many other studies in perennial ryegrass (Louahlia et al, 2008), Arabidopsis (Krapp et al, 2011), wheat (Howarth et al, 2008), tomato (Urbanczyk-Wochniak and Fernie, 2005), and tobacco (Fritz et al, 2006). Under control growth conditions (sufficient N, S-N), 'Pushu 53' had higher lysine (Lys), phenylalanince (Phe), glycine (Gly), and histidine (His) content than 'Tainong 71' (Table 4).…”
Section: Resultssupporting
confidence: 90%
“…Several studies have shown that amino acids (especially glutamine and asparagine) supplied to roots by the phloem are implied in the specific regulation of NO 3 -uptake and in its coordination with photosynthesis (Muller and Touraine 1992;Delhon et al 1996;Malagoli et al 2004;Louahlia et al 2008). A feedback regulation of NO 3 -uptake by the N demand of the plant was also observed in N 2 fixing clover lines .…”
Section: Nitrogen Supplymentioning
confidence: 88%